General practitioner service provision in residential aged care facilities: 1998–2011. (5th November 2012) - Taylor, Michael J; Edvardsson, David; Horey, Dell; Fetherstonhaugh, Deirdre; Nay, Rhonda; Swerissen, Hal
The pattern of GP services provided in RACFs has changed substantially over time. To some extent these changes reflect regulatory adjustments; however, the pattern is at odds with the ever‐increasing dependence levels of residents.